KOMUNIKASI INTERPERSONAL KEPALA MADRASAH DAN IMPLIKASINYA TERHADAP KINERJA TENAGA PENDIDIK DAN KEPENDIDIKAN - Pauji, Ade Ikbal (Institut Nahdlatul Ulama Tasikmalaya, 2025)
The performance of teaching and educational staff is a key determinant in achieving the objectives of educational institutions. One contributing factor to improving such performance is the interpersonal communication of the principal (head of madrasah). This study aims to describe and analyze the practice of principals’ interpersonal communication, its supporting and inhibiting factors, and its implications for the performance of teaching and educational staff. The research employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, and analyzed using descriptive-analytical techniques. The findings reveal that principals’ interpersonal communication is manifested through openness, support, empathy, expressiveness, and equality. Supporting factors include message clarity, ease of understanding, and communicants’ maturity of thought, while inhibiting factors involve physical and semantic barriers. Furthermore, principals’ interpersonal communication functions as a controlling instrument and a source of work motivation, thereby enhancing the performance of teaching and educational staff. These findings underscore the significance of principals’ interpersonal communication competence as an essential managerial strategy in educational human resource development.